Analysis of the Effect of Financial Performance on Stock Prices in Consumer Sector Manufacturing Companies Listed on The Indonesia Stock Exchange for the Period 2017 – 2022 - Fadila, Zakia; Hou, Amin; Harianto, Adi; Pasaribu, Deby Siska Oktavia; Hirzi, M. Fakhrul (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to analyze the effect of financial performance on stock prices in consumer sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2017 - 2022. The method used by the author in this study uses descriptive quantitative research methods. This descriptive qualitative research is to determine the effect of financial performance on stock prices in consumption sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2017 - 2022. Population identification in this study is the consumer goods industry sector of the food and beverage industry subsector totaling 26 companies. The sample in this study amounted to 7 food and beverage industry sector companies listed on the IDX 2024. Data analysis in this study used the Structural Equation Model Partial Least Square (SEM-PLS). The results of this study are partially ROE has no positive and insignificant effect on stock prices in Consumer Sector Manufacturing Companies Listed on the Indonesia Stock Exchange for the period 2017 - 2022, 2) partially ROA has a positive and insignificant effect on stock prices in Consumer Sector Manufacturing Companies Listed on the Indonesia Stock Exchange for the period 2017 - 2022, 3) partially DER has a positive and insignificant effect on stock prices in Consumer Sector Manufacturing Companies Listed on the Indonesia Stock Exchange for the period 2017 - 2022. 4) simultaneously ROE, ROA and DER have a positive and insignificant effect on stock prices in Consumer Sector Manufacturing Companies Listed on the Indonesia Stock Exchange for the period 2017 - 2022